An Analysis of Maxim in Novel “Me Before You” by Jojo Moyes - Romanna Romanna; Gaguk Rudianto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This study aims to determine what maxim is dominant in a novel entitled "Me Before You" by Jojo Moyes. This study was investigated using the Gricean pragmatic theory. This type of research is a qualitative descriptive study and the data used are the utterances contained in the novel Me Before You by Jojo Moyes which there are four maxim,  maxim of quality, maxim of quantity, maxim of relation, and maxim of manner which they are intended as cooperative principle by Yule. After do the research the researcher found quality is the maxim that is more widely used